Low plasma concentrations of apolipoprotein M are associated with disease activity and endothelial dysfunction in systemic lupus erythematosus - Tydén, Helena (Arthritis Res Ther, 2019)
BACKGROUND: Apolipoprotein M (apoM) is a 25-kDa apolipoprotein present in 5% of high-density lipoprotein (HDL) particles. It is suggested to be anti-atherogenic and to play a key role in sustaining endothelial barrier integrity. SLE patients have increased cardiovascular disease risk, and we aimed to investigate if apoM levels reflect endothelial function in SLE. Since apoM plasma levels decrease during inflammatory conditions, our aim was also to determine the impact of SLE disease activity on apoM plasma levels. METHODS: Plasma concentrations of apoM were measured by ELISA in two patient groups with systemic lupus erythematosus (SLE) and in 79 healthy control individuals. In patient group I (n = 84), evaluation time points were selected with the objective to include a wide range of clinical and laboratory variables reflecting disease activity which was measured as SLEDAI. In patient group II consisting of 140 consecutive patients, endothelial function was measured by a finger plethysmograph. A low Reactive Hyperemia Index (RHI) value indicates endothelial dysfunction. RESULTS: SLE patients had decreased levels of apoM compared to healthy controls (p < 0.01), with apoM levels correlating inversely with SLEDAI (r = − 0.31, p < 0.01) as well as with levels of CRP (r = − 0.26, p = 0.02) and positively with levels of C3 (r = 0.29, p < 0.01). ApoM levels were particularly low in patients with active disease from the kidney and skin and in patients with leukopenia or positive anti-dsDNA antibody test (p < 0.05). ApoM levels correlated with RHI values in young SLE patients (r = 0.32, p = 0.01), consistent with the important role of apoM in regulating endothelial integrity. CONCLUSIONS: ApoM levels may be regulated by SLE-related inflammatory processes and could be a marker of disease activity and endothelial dysfunction, in particular in young SLE patients. Further studies are needed to investigate the predictive value of apoM in the development of a cardiovascular disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13075-019-1890-2) contains supplementary material, which is available to authorized users.